Systematic Literature Review: Implementation of Artificial Intelligence in the Field of Management Science - Zulfikar, Muhammad Vicky; Anfi, Dieva Zahrotu; Mardani, Agnes Dini (IJBLE Scientific Publications Community Inc., 2025)
This research aims to identify the implementation of artificial intelligence and in the field of management based on published research articles. Additionally, this study aims to explore gaps in knowledge to contribute to future academic studies. A systematic literature review (SLR) method was employed to analyse various articles published in academic journals indexed in Scopus from 2018 to 2023. Articles were screened using predefined keywords obtained from top-ranked journals. The SLR method was used to review the topics/themes, findings, methodologies, recommendations, and limitations of the published articles. The analysis results provide evidence that the implementation of artificial intelligence and in management enhances the effectiveness and efficiency of management. It is important to encourage the adoption of this technology to unlock its significant potential, while also considering the ethical aspects of its implementation. This research is expected to be beneficial and contribute to future research development by providing insights and identifying research gaps in the implementation of artificial intelligence and in management